Sensory Perception Quotient Reveals Visual, Scent and Touch Sensory Hypersensitivity in People With Fibromyalgia Syndrome - Dorris, Emma R.; Maccarthy, James; Simpson, Ken; McCarthy, Geraldine M. (Frontiers in Pain Research, 2022)
Background Environmental sensitivity is commonly reported by people with fibromyalgia syndrome. People living with fibromyalgia syndrome frequently report hypersensitivity to noxious and non-noxious sensations. To date, there has been little empirical validation of sensory disturbance to non-noxious triggers. Environmental sensitivity is used as a diagnostic feature only in Bennet's alternative criteria for diagnosis of fibromyalgia, where it was ranked the second most important of the components for diagnosis, after number of pain sites. The aim of this study was to use a validated sensory measure to determine if people with fibromyalgia have greater sensory disturbances compared to people with other chronic pain conditions. Methods This study used the Sensory Perception Quotient (SPQ) 92 question survey in adults with chronic pain conditions. A fibromyalgia group (n = 135) and a non-fibromyalgia chronic pain control group (n = 45) were recruited. All participants completed the SPQ as a self-report measure of sensory processing. In addition to the original SPQ scoring method, the Revised Scoring of the Sensory Perception Quotient (SPQ-RS) method was used to investigate self-reported hypersensitivity and hyposensitivity and the vision, hearing, taste, touch, and smell subscales. Chi-squared tests were used for categorical variables and Mann Whitney U, or Kruskal-Wallis H test were used to compare groups. Results The fibromyalgia group reported significantly more sensitivity compared to the control group (p = 0.030). The fibromyalgia group reported significantly greater hypersensitivity (p = 0.038), but not more hyposensitivity (p = 0.723) compared to controls. The average fibromyalgia SPQ score (92.64 ± 23.33) was similar to that previously reported for adults with autism (92.95 ± 26.61). However, whereas adults with autism had broad range hypersensitivity, the fibromyalgia group reported significantly more hypersensitivity compared to the control group, but the range was restricted to vision (p = 0.033), smell (p = 0.049) and touch (0.040). Conclusions These findings demonstrate greater sensory hypersensitivity in people with fibromyalgia compared to people with other chronic pain disorders. Greater hypersensitivity was restricted to touch, vision, and smell, all of which have previously been demonstrated to crosstalk with nociception.